Remgro : distributing its tobacco interests - Mitchell, Clare (SAGE knowledge. Cases., 2016)
In 2008 Remgro Limited (Remgro) completed the distribution of its indirect shareholding in British American Tobacco plc (BAT): 90% of its shares had gone to its shareholders, while the balance of 10% went to a new investment vehicle listed on the Luxembourg Stock Exchange, called Reinet Investments. This book examines the process.